Effect of intercalated molybdenum atoms on structure and electrochemical properties of Mo1+xS2 synthesized by hydrothermal method. (11th June 2023) - Jia, Zhenggang; Bai, Congyan; Zhang, Xuexi; Qian, Mingfang; Tsai, Hsu-Sheng; Xiong, Yueping
Abstract: As an alternative anode to graphene, molybdenum disulfide (MoS2 ) has attracted much attention due to its layered structure and high specific capacity. Moreover, MoS2 can be synthesized by hydrothermal method with low cost and the size of its layer spacing can be controlled. In this work, the results of experiment and calculation proved that the presence of intercalated Mo atoms, leading to the expansion of MoS2 layer spacing and weakening of Mo–S bonding. For the electrochemical properties, the presence of intercalated Mo atoms causes the lower reduction potentials for the Li + intercalation and Li2 S formation. In addition, the effective reduction of diffusion resistance and charge transfer resistance in Mo1+ x S2 leads to the acquisition of high specific capacity for battery applications.